Method for producing polyarylene sulfide resin composition
By adding and condensing alkoxysilane compounds into the polyaryl sulfide resin and adding an alkaline carbonate inorganic filler, the process conditions are optimized, and the leakage and forming properties of the polyaryl sulfide resin composition under low melt viscosity are solved. The problem is that the improvement of melt viscosity and the improvement of continuous forming properties have been achieved.
Patent Information
- Application Number
- CN202280052450.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-30
- Filing Date
- 2022-07-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-07-11
AI Technical Summary
When using low melt viscosity polyarylene sulfide resins and alkoxysilane compounds, the melt viscosity of the composition is prone to decrease, resulting in an increase in leakage during injection molding, affecting production efficiency and continuous forming properties of the molded product, especially in the containing The problem is even more serious when it comes to inorganic fillers of alkaline carbonates.
By adding an appropriate amount of alkoxysilane compound to the polyarylene sulfide resin and partially condensate, the ratio of the condensate is controlled to be 0.5 to 60 mass%, and then adding alkaline carbonate inorganic filling during the melt-kneading process The agent is optimized for process conditions such as cylinder temperature and rotational speed to improve the melt viscosity and continuous forming properties of the composition.
Under low melt viscosity conditions, the melt viscosity of the polyarylene sulfide resin composition is achieved, reducing the leakage during injection molding, and improving the production efficiency and continuous forming properties of the molded product.
Smart Images

Figure BDA0004682792310000161 
Figure BDA0004682792310000171
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a polyarylene sulfide resin composition. Background Art
[0002] Polyphenylene sulfide (hereinafter also referred to as PPS) resin, which is a type of polyarylene sulfide (hereinafter also referred to as PAS) resin, has high heat resistance, mechanical properties, chemical resistance, and flame retardancy. Therefore, it is widely used in various automotive parts, electrical / electronic equipment parts, etc., mainly for extrusion molding / injection molding.
[0003] Various additives are added to PAS resin compositions to improve various properties. Among such additives, it has been proposed to add alkoxysilane compounds for the purpose of improving toughness (see Patent Documents 1 and 2).
[0004] Patent Document 1 describes a method for producing a polyarylene sulfide resin composition, in which an olefin-based copolymer and an alkoxysilane compound are added to a PAS resin in order to improve toughness and formability in a low temperature environment. In addition, Patent Document 2 describes a method for producing a polyarylene sulfide resin composition, in which an alkoxyaminosilane is added to a PPS resin for the purpose of improving toughness and welding strength. When an alkoxysilane compound such as an alkoxyaminosilane reacts with water (water in the air, etc.), a condensation reaction between the alkoxysilane compounds occurs before the alkoxysilane compound reacts with the PPS resin, and it is difficult to obtain the desired mechanical properties. Therefore, in Patent Document 2, a PPS resin that has been dried in advance is used.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2019 / 026869
[0008] Patent Document 2: International Publication No. 2012 / 147185 Summary of the invention
[0009] Problems to be solved by the invention
[0010] As mentioned above, toughness is usually improved by adding an alkoxysilane compound to a PAS resin composition. Such toughness improvement is due to the increase in melt viscosity by adding an alkoxysilane compound. However, when a PAS resin with a low melt viscosity (80Pa·s or less) is used, the melt viscosity of the PAS resin composition tends to be lower. In particular, when a condensate of an alkoxysilane compound is present, it can be considered that the effect of increased melt viscosity achieved by the addition of the alkoxysilane compound cannot be achieved, and the melt viscosity tends to further decrease. Moreover, since the PAS resin composition has high fluidity when the melt viscosity is low, during injection molding, the PAS resin composition sometimes leaks from the front end of the nozzle of the injection molding machine after molding until the next molding cycle begins. When the amount of leakage of the PAS resin composition is large, it is necessary to perform new molding after removing the leaked PAS resin composition, so the production efficiency of the molded product using the PAS resin composition is low and the continuous moldability of the molded product decreases, which becomes a problem. The present inventors have also found that when a basic carbonate such as calcium carbonate is contained as an inorganic filler, the amount of leakage of the PAS resin composition is particularly large and the continuous moldability of the molded product is significantly reduced.
[0011] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a method for producing a polyarylene sulfide resin composition having excellent continuous moldability while using a polyarylene sulfide resin having a low melt viscosity, an alkoxysilane compound and a basic carbonate in combination.
[0012] Solutions to Solve Problems
[0013] The present invention has been accomplished based on the finding that, when a basic carbonate-containing inorganic filler is contained, leakage of a PAS resin composition during injection molding is significant, and the cause of this leakage is water in the PAS resin composition.
[0014] One mode of the present invention for achieving the above-mentioned object is as follows.
[0015] (1) A method for producing a polyarylene sulfide resin composition, comprising:
[0016] Step A, which is to prepare a masterbatch by mixing 0.2 to 50 parts by mass of an alkoxysilane compound with 100 parts by mass of a polyarylene sulfide resin at a temperature of 310° C. and a shear rate of 1200 sec. -1 The melt viscosity measured under 5-80 Pa·s;
[0017] Step B of condensing a part of the alkoxysilane compound in the masterbatch so that the ratio of the condensate of the alkoxysilane compound is 0.5 to 60 mass % of the alkoxysilane compound; and
[0018] Step C is for melt-kneading raw materials, the raw materials containing the masterbatch obtained in the step B, i.e., the condensate of the alkoxysilane compound having a ratio within the above range, at least one inorganic filler containing a basic carbonate, and other components.
[0019] (2) The method for producing a polyarylene sulfide resin composition according to (1), wherein:
[0020] The method further comprises a step D for preparing a new polyarylene sulfide resin which is the same as or different from the polyarylene sulfide resin used in the step A.
[0021] In the step C, the raw materials including the master batch obtained in the step B and the polyarylene sulfide resin prepared in the step D are melt-kneaded so that the total amount of the alkoxysilane compound and the condensate of the alkoxysilane compound is 0.2 to 3.0 parts by mass based on 100 parts by mass of the total polyarylene sulfide resin.
[0022] (3) The method for producing a polyarylene sulfide resin composition according to (1) or (2), wherein:
[0023] In the step C, the raw materials are melt-kneaded by an extruder, and the cylinder temperature in the extruder is set to 290 to 380°C.
[0024] (4) The method for producing a polyarylene sulfide resin composition according to any one of (1) to (3), wherein
[0025] The content of the inorganic filler in the raw material in the step C is 10 to 315 parts by mass based on 100 parts by mass of the polyarylene sulfide resin composition.
[0026] (5) The method for producing a polyarylene sulfide resin composition according to any one of (1) to (4), wherein
[0027] The alkoxysilane compound includes at least one selected from the group consisting of epoxyalkoxysilane, aminoalkoxysilane, vinylalkoxysilane, and mercaptoalkoxysilane.
[0028] (6) The method for producing a polyarylene sulfide resin composition according to any one of (1) to (5), wherein
[0029] The alkoxysilane compound contains at least one selected from the group consisting of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-diallylaminopropyltrimethoxysilane, and γ-diallylaminopropyltriethoxysilane.
[0030] (7) The method for producing a polyarylene sulfide resin composition according to any one of (1) to (6), wherein
[0031] The melt viscosity of the polyarylene sulfide resin composition is 150 to 600 Pa·s.
[0032] Effects of the Invention
[0033] According to the present invention, it is possible to provide a method for producing a polyarylene sulfide resin composition having excellent continuous moldability while using a polyarylene sulfide resin having a low melt viscosity, an alkoxysilane compound, and a basic carbonate in combination. DETAILED DESCRIPTION
[0034] The present embodiment will be described in detail below, but the present embodiment is not limited to the following embodiments and can be implemented with appropriate changes within the scope of the purpose of the present embodiment.
[0035] In this specification, etc., the masterbatch means a mixture obtained by simply stirring raw materials without heating, melt-kneading, or pelletizing.
[0036] <Method for producing polyarylene sulfide resin composition>
[0037] The method for producing a polyarylene sulfide resin composition of the present embodiment includes step A of preparing a masterbatch by mixing 0.2 to 50 parts by mass of an alkoxysilane compound with 100 parts by mass of a polyarylene sulfide resin at a temperature of 310° C. and a shear rate of 1200 sec -1 The melt viscosity measured under 100°C is 5 to 80 Pa·s. In addition, the method further includes a step B of condensing a part of the alkoxysilane compound in the masterbatch so that the ratio of the condensate of the alkoxysilane compound is 0.5 to 60% by mass of the alkoxysilane compound. The method further includes a step C of melt-kneading a raw material, the raw material comprising the masterbatch obtained in step B, i.e., the masterbatch having a ratio of the condensate of the alkoxysilane compound within the above range, at least one inorganic filler containing an alkaline carbonate, and other components.
[0038] As mentioned above, the inventors have found that when containing alkaline carbonates such as calcium carbonate, the leakage of PAS resin composition is particularly large, and the problem of the continuous formability of the molded product decreasing is significant. It is estimated that the reason is moisture. It is estimated that moisture affects the ratio of the condensate of alkoxysilane compound, and the higher the ratio, the more moisture. Therefore, it is believed that by reducing the condensate of alkoxysilane compound, moisture is reduced, so that the leakage of PAS resin composition can be reduced. However, even if the condensate of alkoxysilane compound is too little, the increase of the melt viscosity of PAS resin composition can be seen, therefore according to the balance of the leakage of PAS resin composition and melt viscosity, the ratio of the condensate of alkoxysilane compound as described above is specified.
[0039] Each step is described below.
[0040] [Process A]
[0041] In step A, a masterbatch is prepared by mixing 0.2 to 50 parts by mass of an alkoxysilane compound with 100 parts by mass of a PAS resin, wherein the PAS resin is heated at a temperature of 310° C. and a shear rate of 1200 sec. -1 The melt viscosity measured under 370°C is 5 to 80 Pa·s.
[0042] When the content of the alkoxysilane compound mixed in the preparation of the masterbatch is 0.2 to 50 parts by mass relative to 100 parts by mass of the PAS resin, it is easy to adjust the ratio of the condensate of the alkoxysilane compound in the masterbatch to the alkoxysilane compound to a predetermined ratio. In addition, the clogging of the pipe can be suppressed and the handling is easy. The content of the alkoxysilane compound is 0.2 to 50 parts by mass relative to 100 parts by mass of the PAS resin, preferably 0.3 to 25 parts by mass, more preferably 0.5 to 15 parts by mass, and further preferably 1.0 to 10 parts by mass.
[0043] Examples of a method for preparing the masterbatch include a method of dry-blending a PAS resin and an alkoxysilane compound, and a mixing method using a tumbler or a Henschel mixer is preferred.
[0044] The raw materials used in step A are described below.
[0045] [raw material]
[0046] (Polyarylene sulfide resin)
[0047] PAS resin is a resin mainly composed of -(Ar-S)- as a structural unit (Ar represents an arylene group). In this embodiment, a polyarylene sulfide resin with a generally known molecular structure can be used. For example, as the arylene group, phenylene such as p-phenylene, m-phenylene and o-phenylene, p,p'-biphenylene, p,p'-diphenylene ether, p,p'-diphenylene carbonyl, p,p'-diphenylene sulfonyl and naphthylene can be used.
[0048] The PAS resin may be a homopolymer using the same structural unit among the structural units represented by -(Ar-S)-, or a copolymer containing different kinds of structural units depending on the application.
[0049] As the homopolymer, a homopolymer having p-phenylene as an arylene group and a p-phenylene sulfide group as a structural unit is preferred. This is because a homopolymer having a p-phenylene sulfide group as a structural unit has extremely high heat resistance and exhibits high strength, high rigidity, and higher dimensional stability in a wide temperature range. By using such a homopolymer, a molded article having extremely excellent physical properties can be obtained.
[0050] As the copolymer, a combination of two or more different arylene sulfide groups among the above-mentioned arylene group-containing arylene sulfide groups can be used. Among them, a combination containing a p-phenylene sulfide group and an m-phenylene sulfide group is preferred from the viewpoint of obtaining a molded product having high physical properties such as heat resistance, moldability, and mechanical properties.
[0051] A polymer containing 70 mol% or more of p-phenylene sulfide groups is more preferred, and a polymer containing 80 mol% or more of p-phenylene sulfide groups is still more preferred. The PAS resin having a phenylene sulfide group is a polyphenylene sulfide resin (PPS resin).
[0052] Generally, it is known that PPS resin has a substantially linear molecular structure without branching or cross-linking and a structure with branching or cross-linking, depending on its production method. However, any type can be used as PAS resin.
[0053] From the perspective of toughness and fluidity, the melt viscosity of PAS resin at a temperature of 310°C and a shear rate of 1200 sec -1 The melt viscosity of the PAS resin is preferably 7 to 70 Pa·s, more preferably 10 to 60 Pa·s, and even more preferably 13 to 50 Pa·s.
[0054] In addition, the present embodiment solves the problem of decreased continuous moldability that may occur when using a PAS resin having a melt viscosity of 80 Pa·s or less and an alkoxysilane compound. Therefore, a PAS resin having a melt viscosity of more than 80 Pa·s is not included in the present embodiment.
[0055] (Alkoxysilane compound)
[0056] The alkoxysilane compound is not particularly limited, and examples thereof include epoxyalkoxysilane, aminoalkoxysilane, vinylalkoxysilane, and mercaptoalkoxysilane, and one or more thereof may be used. The alkoxy group preferably has 1 to 10 carbon atoms, and more preferably 1 to 4 carbon atoms.
[0057] Examples of epoxyalkoxysilane include γ-glycidoxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and γ-glycidoxypropyltriethoxysilane.
[0058] Examples of aminoalkoxysilanes include γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-diallylaminopropyltrimethoxysilane, γ-diallylaminopropyltriethoxysilane, and the like. One or more of these may be used.
[0059] Examples of the vinylalkoxysilane include vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltri(β-methoxyethoxy)silane.
[0060] Examples of the mercaptoalkoxysilane include γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane.
[0061] Among them, epoxyalkoxysilane and aminoalkoxysilane are preferred, and γ-aminopropyltriethoxysilane is particularly preferred.
[0062] [Process B]
[0063] In step B, a part of the alkoxysilane compound in the masterbatch is condensed so that the ratio of the condensate of the alkoxysilane compound becomes 0.5 to 60 mass % of the alkoxysilane compound.
[0064] From the perspective of obtaining excellent continuous moldability of the PAS resin composition, the ratio of the condensate among the alkoxysilane compounds in the masterbatch is 0.5 to 60% by mass. The ratio of the condensate is preferably 0.6 to 50% by mass, and more preferably 0.7 to 45% by mass. In addition, when the ratio of the condensate is less than 0.5% by mass, when the amount of the inorganic filler in the PAS resin composition is large, the melt viscosity may become too high.
[0065] The amount of the condensate of the alkoxysilane compound depends on the amount of the hydrolyzed alkoxysilane compound. Examples of methods for adjusting the amount of the condensate of the alkoxysilane compound include the following (1) to (3).
[0066] (1) Adjust the humidity of the environment where the alkoxysilane compound and the masterbatch are stored and the water vapor transmission rate of the system.
[0067] (2) Adjust the storage time of the alkoxysilane compound and the masterbatch.
[0068] (3) The mixing ratio of the PAS resin and the alkoxysilane compound in the masterbatch in step A is adjusted.
[0069] As a specific example, for example, a masterbatch in step A is prepared by mixing 2 parts by mass of an alkoxysilane compound with 100 parts by mass of a PAS resin, and the amount of the condensate is 43% by mass when the mixture is stored at a temperature of 40° C. and a humidity of 80% RH for 40 minutes. In addition, a masterbatch in step A is prepared by mixing 25 parts by mass of an alkoxysilane compound with 100 parts by mass of a PAS resin, and the amount of the condensate is 1% by mass when the mixture is stored at a temperature of 23° C. and a humidity of 40% RH for 10 minutes. When the amount of the condensate of the alkoxysilane compound is 0.5 to 60% by mass, a PAS resin composition having excellent continuous formability can be obtained.
[0070] Furthermore, even after the condensate of the alkoxysilane compound is generated by the methods (1) to (3), the ratio of the condensate can be adjusted by newly adding an alkoxysilane compound to adjust the amount of the condensate of the alkoxysilane compound. For example, even if the ratio of the condensate exceeds 60% by mass, the ratio of the condensate can be finally adjusted to 0.5 to 60% by mass by further adding an alkoxysilane compound.
[0071] In addition, in the final product, the PAS resin composition, the condensate of the alkoxysilane compound condensed by reaction with the PAS resin and the condensate of the alkoxysilane compound condensed by reaction with water cannot be distinguished. Therefore, it is necessary to adjust the amount of the condensate of the alkoxysilane compound condensed by reaction with water in the state of the masterbatch.
[0072] Here, an example of a method for calculating the ratio of the condensate of the alkoxysilane compound in the masterbatch will be described.
[0073] The masterbatch contains at least a PAS resin, an alkoxysilane compound, and a condensate of the alkoxysilane compound produced by hydrolysis of the alkoxysilane compound.
[0074] Furthermore, the alkoxysilane compound is soluble in acetone, whereas the condensate of the alkoxysilane compound is insoluble in acetone.
[0075] First, the mass A of the aluminum cup is measured using a precision balance (step 1).
[0076] Next, the aluminum cup is placed on a precision balance and zeroed, and then a membrane filter is placed on the aluminum cup and the mass B of the membrane filter is measured (step 2). Next, the weighed membrane filter is placed in a suction funnel (step 3). At this time, there is only the aluminum cup on the precision balance.
[0077] Next, the masterbatch is placed in an aluminum cup and the mass C is measured (step 4). Next, the weighed masterbatch is placed in a funnel equipped with a membrane filter. The aluminum cup is cleaned with acetone and the cleaning liquid is also placed in the funnel (step 5).
[0078] Next, while cleaning the periphery of the funnel, acetone was added, stirred with a spatula for about 3 seconds, and then suction filtered. The following steps of adding acetone, stirring with a spatula, and then suction filtering were performed twice more (step 6).
[0079] Next, the residue and the membrane filter were placed on an aluminum cup, dried at 40° C. for 2 hours using a vacuum dryer, and the mass D was measured (step 7).
[0080] The ratio of the condensate in the alkoxysilane compound is represented by the following formula.
[0081] Condensate ratio (mass %) = (mass of condensate in the alkoxysilane compound contained in the masterbatch / mass of the alkoxysilane compound prepared when preparing the masterbatch) × 100 = {[{mass D - (mass A + mass B)} - mass C × (1-EF)] / (mass C × E)} × 100
[0082] In the above formula, E represents the concentration (g / g) of the alkoxysilane compound in the masterbatch, and F represents the concentration (g / g) of substances dissolved in acetone other than the alkoxysilane compound in the masterbatch.
[0083] Through the above steps, the ratio of the condensate of the alkoxysilane compound in the masterbatch can be calculated.
[0084] In this embodiment, a part of the alkoxysilane compound in the masterbatch prepared in step A is condensed in step B. However, when the period between step A and step B is long, it is preferably stored in a dry state so as not to cause a condensation reaction due to moisture. In this embodiment, since an inorganic filler containing an alkaline carbonate is contained, leakage of the PAS resin composition during injection molding is not likely to occur, especially due to the influence of moisture. Therefore, it is particularly important to store the masterbatch in a dry state.
[0085] Alternatively, when the period until step C is long after step A and step B are completed, it is preferred to store in a dry state so that the ratio of the condensate in the masterbatch obtained in step B does not change.
[0086] However, even if the ratio of the condensate in the masterbatch changes, as long as the amount of the condensate in the masterbatch when fed into the extruder satisfies the prescribed range, it will suffice. For example, when the ratio of the condensate in the condensate in the masterbatch increases, the ratio of the condensate can be lowered by newly adding an alkoxysilane compound when feeding into the extruder.
[0087] [Process C]
[0088] In step C, raw materials including the masterbatch obtained in step B, namely, the condensate of the alkoxysilane compound having a ratio within the above range, at least one inorganic filler containing a basic carbonate, and other components are melt-kneaded.
[0089] (Inorganic filler)
[0090] In this embodiment, from the perspective of improving mechanical properties, at least one inorganic filler containing alkaline carbonate is contained in the PAS resin composition. As inorganic fillers other than alkaline carbonates, fibrous inorganic fillers (but excluding alkaline carbonates), powdery inorganic fillers (but excluding alkaline carbonates), and plate-like inorganic fillers (but excluding alkaline carbonates) can be listed. Moreover, one of them can be used, or two or more of them can be used in combination.
[0091] Examples of the alkaline carbonate include calcium carbonate, magnesium carbonate, sodium carbonate, potassium carbonate, ammonium carbonate, and zinc carbonate.
[0092] Examples of commercially available calcium carbonate include whiten P-30 (average particle size (50% d): 5 μm) manufactured by Toyo Fine Chemical Co., Ltd.
[0093] In the present embodiment, when the content of the basic carbonate is 0.5 to 315 parts by mass based on 100 parts by mass of the PAS resin, the effect of reducing leakage of the PAS resin composition during injection molding can be exhibited.
[0094] Next, inorganic fillers other than the basic carbonate will be described.
[0095] As fibrous inorganic fillers other than alkaline carbonate, mineral fibers such as glass fiber, carbon fiber, zinc oxide fiber, titanium oxide fiber, wollastonite, silica fiber, silica-alumina fiber, zirconium oxide fiber, boron nitride fiber, silicon nitride fiber, boron fiber, potassium titanate fiber, and metal fibrous materials such as stainless steel fiber, aluminum fiber, titanium fiber, copper fiber, and brass fiber can be listed, and one or more of them can be used. Among them, glass fiber is preferred.
[0096] Examples of commercially available glass fiber products include chopped glass fiber (ECS03T-790DE, average fiber diameter: 6 μm) manufactured by Nippon Electric Glass Co., Ltd., chopped glass fiber (CS03DE 416A, average fiber diameter: 6 μm) manufactured by Owens Corning Japan (Co., Ltd.), chopped glass fiber (ECS03T-747H, average fiber diameter: 10.5 μm) manufactured by Nippon Electric Glass Co., Ltd., chopped glass fiber (ECS03T-747, average fiber diameter: 13 μm) manufactured by Nippon Electric Glass Co., Ltd., special-shaped cross-section chopped strand CSG3PA-830 (long diameter 28 μm, short diameter 7 μm) manufactured by Nitto Bosho Co., Ltd., and special-shaped cross-section chopped strand CSG3PL-962 (long diameter 20 μm, short diameter 10 μm) manufactured by Nitto Bosho Co., Ltd.
[0097] The fibrous inorganic filler can be surface treated by various surface treatment agents such as commonly known epoxy compounds, isocyanate compounds, silane compounds, titanate compounds, fatty acids, etc. The surface treatment can improve the adhesion with the PAS resin. The surface treatment agent can be applied to the fibrous inorganic filler in advance before the material is prepared to perform surface treatment or convergence treatment, or it can be added simultaneously during the material preparation.
[0098] The fiber diameter of the fibrous inorganic filler is not particularly limited, but in the initial shape (shape before melt kneading), it can be, for example, 5 μm or more and 30 μm or less. Here, the fiber diameter of the fibrous inorganic filler refers to the major axis of the fiber cross section of the fibrous inorganic filler.
[0099] As the powdery particulate inorganic filler other than the alkaline carbonate, talc (granular), carbon black, silicon dioxide, quartz powder, glass beads, glass powder, silicates such as calcium silicate, aluminum silicate, diatomaceous earth, metal oxides such as iron oxide, titanium oxide, zinc oxide, aluminum oxide (granular), metal sulfates such as calcium sulfate, barium sulfate, other silicon carbide, silicon nitride, boron nitride, various metal powders, etc. can be listed, and one or more of them can be used. Among them, glass beads are preferred.
[0100] Examples of commercially available glass beads include EGB731A manufactured by Potters-Ballotini Co., Ltd. (average particle size (50% d): 20 μm) and EMB-10 manufactured by Potters-Ballotini Co., Ltd. (average particle size (50% d): 5 μm).
[0101] The particulate inorganic filler may also be surface treated in the same manner as the fibrous inorganic filler.
[0102] Examples of plate-like inorganic fillers other than alkaline carbonates include glass flakes, talc (plate-like), mica, kaolin, clay, alumina (plate-like), and various metal foils, and one or more of these can be used. Among them, glass flakes and talc are preferred.
[0103] Examples of commercially available glass sheets include REFG-108 manufactured by Nippon Sheet Glass Co., Ltd. (average particle size (50% d): 623 μm), thin sheets manufactured by Nippon Sheet Glass Co., Ltd. (average particle size (50% d): 169 μm), REFG-301 manufactured by Nippon Sheet Glass Co., Ltd. (average particle size (50% d): 155 μm), and REFG-401 manufactured by Nippon Sheet Glass Co., Ltd. (average particle size (50% d): 310 μm).
[0104] Examples of commercially available talc products include crown talc PP manufactured by Matsumura Sangyo Co., Ltd. and talc PKNN manufactured by Hayashi Kasei Co., Ltd.
[0105] The plate-like inorganic filler may also be surface-treated in the same manner as the fibrous inorganic filler.
[0106] In the present embodiment, the inorganic filler other than the alkaline carbonate is preferably one or more selected from the group consisting of glass fibers, glass beads, glass flakes, and talc.
[0107] In addition, from the perspective of improving mechanical properties, it is preferred that the inorganic filler containing the alkaline carbonate is contained in an amount of 10 to 315 parts by mass relative to 100 parts by mass of the PAS resin contained in the PAS resin composition. That is, the content of the inorganic filler in the raw material in step C is preferably 10 to 315 parts by mass relative to 100 parts by mass of the PAS resin. The content of the inorganic filler is more preferably 20 to 300 parts by mass, further preferably 30 to 280 parts by mass, and particularly preferably 35 to 250 parts by mass.
[0108] As other components, PAS resin prepared separately and / or other additives described later other than the inorganic filler etc. are mentioned. Among them, PAS resin is demonstrated in step D.
[0109] Inorganic fillers and other ingredients can also be added when PAS resin and masterbatch are prepared for melt mixing. In addition, inorganic fillers and other additives and masterbatch can be mixed by dry blending and the resulting mixture can be mixed with PAS resin for melt mixing.
[0110] In order to melt-knead the raw materials containing the masterbatch, the inorganic filler and other components, for example, the masterbatch, the inorganic filler and other components can be supplied to the extruder separately. Alternatively, the masterbatch, the inorganic filler and other components can be supplied to the extruder after dry mixing. Moreover, a part of the raw materials can be supplied in the form of side feeding.
[0111] On the other hand, the inventors have found that when the PAS resin composition contains an alkaline carbonate, by further increasing the amount of heat received by the PAS resin composition during melt kneading in step C, the amount of PAS resin composition leaking from the nozzle tip of the injection molding machine can be further suppressed during subsequent injection molding, after molding, and until the start of the next molding cycle. It is speculated that this is because in addition to the moisture described above, the amount of CO2 generated during molding also contributes to the leakage of the PAS resin composition. It is considered that CO2 is generated by the reaction of acidic gas derived from PAS resin and alkaline carbonate. Moreover, it is also speculated that by increasing the amount of heat given to the PAS resin composition during melt kneading, the amount of CO2 generated during molding can be suppressed. Therefore, in order to increase the amount of heat given to the PAS resin composition during melt kneading, it is preferred that in step C, the raw materials are melt kneaded by an extruder, and the cylinder temperature in the extruder is set to 290 to 380°C. That is, it is preferred to set the set temperature of the cylinder of the extruder during melt kneading within the above range.
[0112] In addition, in order to increase the amount of heat given to the PAS resin composition during melt kneading, the raw materials can be melt kneaded by an extruder, and the speed of the cylinder of the extruder can be increased. Or the screw design of the extruder can be changed to a design that generates higher heat for the PAS resin composition during melt kneading. The cylinder temperature is preferably above 290°C, more preferably above 300°C, particularly preferably above 310°C, more particularly preferably above 320°C, and further preferably above 330°C. In addition, it is preferably below 380°C, more preferably below 370°C. In addition, regarding the speed of the cylinder, since the preferred speed is not uniquely determined according to the ejection volume and the size of the extruder, it cannot be generalized. But for example, in the case of an extruder with a cylinder diameter of 30 mm, Q (kg / h) (ejection volume) / Ns (rpm) (screw speed) is preferably 0.07 to 0.20.
[0113] The PAS resin and the masterbatch are preferably mixed and melt-kneaded so that at the end of step C, the total amount of the alkoxysilane compound and the condensate of the alkoxysilane compound in the finally obtained PAS resin composition is 0.2 to 3.0 parts by mass based on 100 parts by mass of the PAS resin.
[0114] In step C, when a raw material containing a PAS resin is used as other components, it is preferable to provide the following step D.
[0115] [Process D]
[0116] In step D, a new polyarylene sulfide resin which is the same as or different from the polyarylene sulfide resin used in step A is prepared. Then, in step C, a raw material containing the master batch obtained in step B and the polyarylene sulfide resin prepared in step D is melt-kneaded so that the total amount of the alkoxysilane compound and the condensate of the alkoxysilane compound is 0.2 to 3.0 parts by mass based on 100 parts by mass of the total polyarylene sulfide resin. In addition, the total PAS resin refers to the PAS resin used for preparing the master batch in step A and the new PAS resin used in step D.
[0117] The new PAS resin prepared in step D may be the same as or different from the PAS resin used in step A. As examples of the new PAS resin prepared in step D being different from the PAS resin used in step A, the melt viscosity of each PAS resin is different, the molecular structure of each PAS resin is different, etc. Examples of the difference in molecular structure include the following (1) to (3), etc.
[0118] (1) A substance having a substantially linear molecular structure without branching or cross-linking is different from a substance having a branching or cross-linking structure.
[0119] (2) Homopolymers and copolymers are different.
[0120] (3) The arylene sulfide groups of the structural units are different (for example, the p-phenylene sulfide group and the m-phenylene sulfide group are different).
[0121] Preferably, in step C, the total amount of the alkoxysilane compound and the condensate of the alkoxysilane compound mixed into the final PAS resin composition is 0.2 to 3.0 parts by mass relative to 100 parts by mass of the PAS resin. By mixing in this way, the fluidity and toughness of the PAS resin composition can be imparted in a balanced manner. In addition, the adhesion to the inorganic filler is improved, and the mechanical properties are easily improved. In the final PAS resin composition, the total amount of the alkoxysilane compound and the condensate of the alkoxysilane compound is more preferably 0.3 to 2.0 parts by mass relative to 100 parts by mass of the PAS resin, and further preferably 0.5 to 1.5 parts by mass.
[0122] In addition, from the perspective of improving moldability, the melt viscosity of the PAS resin composition is preferably 310°C and a shear rate of 1000 sec. -1 Under the conditions of , it is 150 to 600 Pa·s, more preferably 200 to 500 Pa·s.
[0123] Next, other components used as a part of the raw materials in step C will be described.
[0124] (Other additives, etc.)
[0125] The PAS resin composition can contain known additives added to thermoplastic resins and thermosetting resins according to the required performance, in order to impart the desired characteristics corresponding to its purpose, within the scope of not hindering the effect achieved by the present embodiment (specifically, excellent continuous formability). As additives, burr inhibitors (but except alkoxysilane compounds), mold release agents, lubricants, plasticizers, flame retardants, colorants such as dyes or pigments, crystallization promoters, crystallization nucleating agents, various antioxidants, heat stabilizers, weathering stabilizers, preservatives, etc. can be listed. As burr inhibitors (but except alkoxysilanes), for example, branched polyphenylene sulfide-based resins with very high melt viscosity, such as those described in International Publication No. 2006 / 068161 and International Publication No. 2006 / 068159, etc. can be listed. As mold release agents, polyethylene wax, fatty acid esters, fatty acid amides, etc. can be listed. As crystallization nucleating agents, boron nitride, talc, kaolin, carbon black, carbon nanotubes, etc. can be listed. Examples of the antiseptic include zinc oxide, etc. The content of the additives may be 5% by mass or less in the entire resin composition.
[0126] In addition, in addition to the above-mentioned components corresponding to its purpose, other thermoplastic resin components can also be used in a small amount in the PAS resin composition as an auxiliary. As other thermoplastic resins used herein, any resin is acceptable as long as it is a resin that is stable at high temperatures. For example, aromatic polyesters, polyamides, polycarbonates, ABS resins (acrylonitrile-butadiene-styrene copolymerization synthetic resins), polyphenylene oxides (Polyphenylene Oxide), polyalkyl acrylates, polysulfones, polyether sulfones, polyether imides, polyether ketones, fluororesins, liquid crystal polymers, cyclic olefin copolymers, etc., made of aromatic dicarboxylic acids and glycols or oxycarboxylic acids, etc., can be listed. In addition, these thermoplastic resins can also be mixed with more than two to use. The content of other thermoplastic resin components, for example, can be less than 20% by mass in all resin compositions.
[0127] The PAS resin composition in this embodiment can be used for various purposes. For example, the PAS resin composition can be used for various cooling system parts, ignition-related parts, distributor parts, various sensor parts, various actuator parts, throttle parts, power module parts, ECU parts, various connector parts, etc. of automobiles.
[0128] In addition, as other uses, it can be used for home / office electrical product parts such as LEDs, sensors, sockets, terminal boards, printed circuit boards, motor parts, ECU cases, lighting parts, television parts, rice cooker parts, microwave oven parts, iron parts, copier-related parts, printer-related parts, fax machine-related parts, heaters, air-conditioning parts, etc.
[0129] Example
[0130] The present embodiment will be described in more detail below with reference to examples, but the interpretation of the present embodiment is not limited to these examples.
[0131] [Example 1]
[0132] By mixing 100 parts by mass of PPS resin (manufactured by KUREHA Co., Ltd.), Fortron KPS (melt viscosity: 20 Pa·s (shear rate: 1200 sec -1 , 310°C)) and 0.9 parts by mass of an alkoxysilane compound (γ-aminopropyltriethoxysilane ("KBE-903P" manufactured by Shin-Etsu Chemical Co., Ltd.)) to prepare a masterbatch, and expose it to an environment of temperature 40°C and humidity 70%RH for 5 minutes. The ratio of the condensate in the alkoxysilane compound in the masterbatch is 33% by mass. In addition, as described above, the amount of condensate recorded later is prepared by appropriately changing the exposure time in an environment of temperature 40°C and humidity 70%RH.
[0133] Next, 100 parts by mass of the masterbatch prepared in the above manner, 97 parts by mass of glass fiber (manufactured by Owens Corning Japan (Inc.), chopped strand, diameter 10.5 μm, length 3 mm), and 97 parts by mass of calcium carbonate (manufactured by Toyo Fine Chemicals Co., Ltd., whiten P-30, average particle size (50% d): 5 μm) were put into a twin-screw extruder at a cylinder temperature of 290° C. and a cylinder speed of 240 rpm for melt kneading to obtain a resin composition. In addition, the glass fiber was added separately from the side feed portion of the extruder.
[0134] (Measurement of melt viscosity of PPS resin)
[0135] The melt viscosity of the above-mentioned PPS resin was measured in the following manner. In addition, the melt viscosity of the PPS resins obtained in Examples 3 and 4 and Comparative Example 1 was also measured in the following manner.
[0136] A capillary rheometer (capillograph) manufactured by Toyo Seiki Seisaku-sho, Ltd. was used. The flat die is used as a capillary and the measurement is performed at a barrel temperature of 310°C and a shear rate of 1200 sec. -1 The melt viscosity is below.
[0137] [Example 2]
[0138] Each resin composition was obtained under the same conditions as in Example 1 except that the ratio of the condensate in the alkoxysilane compound in the masterbatch was changed to the ratio shown in Table 1.
[0139] [Examples 3, 4, Comparative Example 1]
[0140] By mixing 100 parts by mass of PPS resin (manufactured by KUREHA Co., Ltd.), Fortron KPS (melt viscosity: 20 Pa·s (shear rate: 1200 sec -1 , 310°C)) and 4.6 parts by mass of an alkoxysilane compound (γ-aminopropyltriethoxysilane ("KBE-903P" manufactured by Shin-Etsu Chemical Co., Ltd.)) to prepare a masterbatch, and expose it to an environment of temperature 40°C and humidity 70%RH for 5 minutes. The ratio of the condensate in the alkoxysilane compound in the masterbatch is 29% by mass. In addition, as described above, the amount of condensate recorded later is prepared by appropriately changing the exposure time in an environment of temperature 40°C and humidity 70%RH.
[0141] Next, PPS resin (manufactured by KUREHA Corporation), Fortron KPS (melt viscosity: 20 Pa·s (shear rate: 1200 sec -1, 310°C)), 100 parts by mass of the masterbatch prepared in the above manner, 25.9 parts by mass of glass fiber (Owens Corning Japan (Co., Ltd.), chopped strand, diameter 10.5 μm, length 3 mm), 122 parts by mass of calcium carbonate (Toyo Fine Chemicals Co., Ltd., whiten P-30, average particle size (50% d): 5 μm) were put into a twin-screw extruder at a cylinder temperature of 290°C for melt kneading to obtain a resin composition. In addition, the glass fiber was added separately from the side feed portion of the extruder.
[0142] (Measurement of Melt Viscosity of Resin Composition)
[0143] Each of the obtained resin compositions was subjected to flow measurement using a capillary rheometer manufactured by Toyo Seiki Seisaku-sho, Ltd. The flat die is used as a capillary to measure the pressure drop at a barrel temperature of 310°C and a shear rate of 1000 sec. -1 The melt viscosity is below.
[0144] [evaluate]
[0145] The amount of the resin composition leaking from the nozzle tip of an injection molding machine ("EC60Ni1.5A" manufactured by Toshiba Machine Co., Ltd.) after injection molding was evaluated for each of the obtained resin compositions. The evaluation method is shown below.
[0146] First, adjust the cylinder temperature of the injection molding machine to 310°C. Next, replace the inside of the cylinder with the evaluation sample by purging. Next, perform one injection, empty the inside of the cylinder, measure 30mm under a back pressure of 2MPa, and immediately remove the resin composition leaking from the front end of the nozzle after sucking back 5mm. Measure the mass of the resin composition leaked between ~1 minute after removal. Perform the above measurement 5 times, and define the average value of the measured values as the amount of resin composition leaking from the front end of the nozzle (g / min).
[0147] Table 1 shows the evaluation results of each resin composition.
[0148] [Table 1]
[0149]
[0150] As can be seen from Table 1, as the ratio of the condensate in the alkoxysilane compound in the masterbatch increases, the amount of the PPS resin composition leaking from the nozzle tip increases, and the continuous moldability decreases. Therefore, when the ratio of the condensate in the alkoxysilane compound in the masterbatch is in the range of 0.5 to 60 mass %, a PPS resin composition having excellent continuous moldability can be obtained.
[0151] [Examples 5 to 11]
[0152] Each resin composition was obtained under the same conditions as in Example 1, except that the ratio of the condensate in the alkoxysilane compound in the masterbatch was changed to 30% by mass, and the cylinder temperature and cylinder speed of the twin-screw extruder were changed as shown in Table 2. Then, under the same conditions as in Example 1, the amount of resin composition leaked from the front end of the nozzle (g / min) and the melt viscosity of the resin composition were measured. The measurement results are shown in Table 2. In addition, after the following pretreatment was performed on each of the obtained resin compositions, the CO2 generation was measured by barrier discharge ionization detection gas chromatography. Then, the CO2 generation below 45 μmol / g was set as A, and the CO2 generation above 45 μmol / g and below 55 μmol / g was set as B. The apparatus configurations of barrier discharge ionization detection gas chromatography were HS (headspace sampler, manufactured by PerkinElmer, TurboMatrix HS40) and GC / BID (manufactured by Shimadzu Corporation, GC-2010 Plus and BID-2010 Plus).
[0153] <Pretreatment>
[0154] The particles were freeze-ground and then dried at 140°C for 2 hours, and then heated at 340°C for 15 minutes.
[0155] [Table 2]
[0156]
[0157] According to Table 2, from the comparison between Example 5 and Example 6, Example 7 and Example 8, and Example 9 and Example 10, which have the same cylinder temperature and different cylinder speeds, it can be seen that the more the cylinder speed increases, the less the leakage of the PPS resin composition. In addition, from the comparison between Example 5, Example 7, Example 9 and Example 11, and Example 6, Example 8 and Example 10, which have the same cylinder speed and different cylinder temperatures, it can be seen that the more the cylinder temperature increases, the less the leakage of the PPS resin composition tends to be.
[0158] On the other hand, it is found that the amount of CO 2 generated can be reduced by setting the cylinder temperature to 290 to 380° C., and the amount of CO 2 generated tends to decrease as the cylinder temperature increases or the cylinder speed increases.
Claims
1. A method for producing a polyarylene sulfide resin composition, characterized in that: include: Step A, which is to prepare a masterbatch by mixing 0.5 to 15 parts by mass of an alkoxysilane compound with 100 parts by mass of a polyarylene sulfide resin at a temperature of 310° C. and a shear rate of 1200 sec. -1 The melt viscosity measured under 5-80 Pa·s; Step B of condensing a part of the alkoxysilane compound in the masterbatch so that the ratio of the condensate of the alkoxysilane compound is 0.5 to 60 mass % of the alkoxysilane compound; and Step C is for melt-kneading raw materials, wherein the raw materials contain the masterbatch obtained in the step B, i.e., the condensate of the alkoxysilane compound having a ratio within the above range, at least one inorganic filler containing an alkaline carbonate, and other components, The alkoxysilane compound contains at least one selected from the group consisting of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-diallylaminopropyltrimethoxysilane, and γ-diallylaminopropyltriethoxysilane.
2. The method for producing a polyarylene sulfide resin composition according to claim 1, characterized in that: The method further comprises a step D for preparing a new polyarylene sulfide resin which is the same as or different from the polyarylene sulfide resin used in the step A. In the step C, the raw materials including the master batch obtained in the step B and the polyarylene sulfide resin prepared in the step D are melt-kneaded so that the total amount of the alkoxysilane compound and the condensate of the alkoxysilane compound in the finally obtained polyarylene sulfide resin composition is 0.2 to 3.0 parts by mass based on 100 parts by mass of the total polyarylene sulfide resin.
3. The method for producing a polyarylene sulfide resin composition according to claim 1 or 2, characterized in that: In the step C, the raw materials are melt-kneaded by an extruder, and the cylinder temperature in the extruder is set to 290 to 380°C.
4. The method for producing a polyarylene sulfide resin composition according to claim 1 or 2, characterized in that: The content of the inorganic filler in the raw material in the step C is 10 to 315 parts by mass based on 100 parts by mass of the polyarylene sulfide resin composition.
5. The method for producing a polyarylene sulfide resin composition according to claim 1 or 2, characterized in that: The melt viscosity of the polyarylene sulfide resin composition is 150 to 600 Pa·s.
Citation Information
Patent Citations
Branched polyarylene sulfide resin, process for producing the same, and use thereof as polymeric modifier
WO2006068159A1
Method for producing polyarylene sulfide resin compositions
WO2012147185A1
Polyarylene sulfide resin composition and fuel contact body
WO2019026869A1
Method for producing polyarylene sulfide resin composition
CN102007184A
Polyaryl sulfoether resin composition
CN1931899A